2014
DOI: 10.1186/1471-2458-14-390
|View full text |Cite
|
Sign up to set email alerts
|

HIV serostatus and disclosure: implications for infant feeding practice in rural south Nyanza, Kenya

Abstract: BackgroundThe World Health Organization (WHO) recommends that HIV-infected women practice exclusive breastfeeding (EBF) for the first 6 months postpartum to reduce HIV transmission. The aim of this study was to determine the effects of HIV/AIDS knowledge and other psychosocial factors on EBF practice among pregnant and postpartum women in rural Nyanza, Kenya, an area with a high prevalence of HIV.MethodsData on baseline characteristics and knowledge during pregnancy, as well as infant feeding practices 4–8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
5
34
2
Order By: Relevance
“…In addition to IPV, this study provides evidence from Zambia to the growing body of literature linking women’s disclosure of an HIV-infected status to following the recommended infant feeding practices (Doherty et al, 2007; Doherty, Chopra, Nkonki, Jackson, & Greiner, 2006; Fadnes et al, 2010; Farquhar et al, 2001; Madiba & Letsoalo, 2013; Onono, Cohen, Jerop, Bukusi, & Turan, 2014; Sibeko, Coutsoudis, Nzuza, & Gray-Donald, 2009). Since exclusive breastfeeding is often perceived as being abnormal in Zambia (Omari et al, 2003), disclosing one’s HIV status to the husband/partner may help a woman justify why she is practicing a certain infant feeding strategy as well as garner support from the husband in order to follow the recommend protocols.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to IPV, this study provides evidence from Zambia to the growing body of literature linking women’s disclosure of an HIV-infected status to following the recommended infant feeding practices (Doherty et al, 2007; Doherty, Chopra, Nkonki, Jackson, & Greiner, 2006; Fadnes et al, 2010; Farquhar et al, 2001; Madiba & Letsoalo, 2013; Onono, Cohen, Jerop, Bukusi, & Turan, 2014; Sibeko, Coutsoudis, Nzuza, & Gray-Donald, 2009). Since exclusive breastfeeding is often perceived as being abnormal in Zambia (Omari et al, 2003), disclosing one’s HIV status to the husband/partner may help a woman justify why she is practicing a certain infant feeding strategy as well as garner support from the husband in order to follow the recommend protocols.…”
Section: Discussionmentioning
confidence: 91%
“…The timeline of the present study coincided with major efforts by NASCOP to increase EBF, and differences exist between the current study population of HIV-infected women intending to breastfeed at enrollment, prior study populations, 26,27 and cross-sectional cohorts. 20,21,[35][36][37] The high prevalence of EBF observed in the present study could have been inflated by social desirability bias, as subjects may have felt compelled to over-report EBF in an effort to please the interviewer. This phenomena has been observed in Kenya with mothers reporting higher proportions of EBF when interviewed face-to-face than with audio computerassisted self-interviewing (ACASI).…”
Section: Discussionmentioning
confidence: 99%
“…36 Another cross-sectional study of HIVinfected and -uninfected women during 2011 at three Kenyan facilities found that EBF prevalence was significantly lower among HIV-uninfected mothers, a population not targeted by NASCOP's EBF promotion efforts, than among HIVinfected mothers of infants aged 3, 4, and 5 months. 37 Research in Kenya indicates that HIV-infected women receive more EBF promotion counseling through PMTCT programs than their HIV-uninfected counterparts, 36,37 and qualitative work suggests that this health-service disparity may be leading to stigmatization of EBF as an indicator of maternal HIV infection, which could limit the effectiveness of future EBF promotion initiatives. 36 Recent studies have suggested that long-duration, supportbased interventions that feature frequent visits after delivery, often weekly or biweekly, are among the most successful ways to increase EBF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is even more challenging in societies where EBF is known to be a recommended feeding practice for HIV-positive mothers (Thairu et al, 2005;Buskens et al, 2007). Conversely, HIV status disclosure to a partner and/or family members gave women the needed support to practice EBF, whilst non-disclosure was associated with the practice of mixed feeding within 6 months postpartum (Fadnes et al, 2010;Marembo et al, 2014;Onono et al, 2014).…”
Section: Effect Of Non-disclosure Of Hiv Statusmentioning
confidence: 99%